Exploring the Anti-Malarial Potential of Terminalia brownii Fresen: A Phytochemical and Biological Activity Study - Tijani, Tawakaltu Omolara; Olaiya, Akeem Ayodele; Garba, Dauda; Atiku, Ibrahim; Sule, Muhammed Ibrahim (Sciences of Phytochemistry, 2025)
Terminalia brownii is a widely distributed African tree traditionally used to treat ailments such as cough, malaria, hepatitis, and microbial infections. The growing resistance of Plasmodium falciparum to Artemisinin combination therapy and other antimalarial drugs highlights the need for new therapies with improved potency and fewer side effects. This study analyzed the phytochemical constituents and antiplasmodial activity of T. brownii leaf extracts. The leaves were air-dried, powdered, and macerated in 70% methanol, followed by fractionation with n-hexane, chloroform, and ethyl acetate. Qualitative analysis of the methanol crude extract (MCE) revealed tannins, flavonoids, alkaloids, triterpenes, steroids, saponins, phenols, and cardiac glycosides, but not anthraquinones. Quantitative analysis showed phenols (195.45 mg/g), tannins (156.10 mg/g), and flavonoids (135.10 mg/g) as the most abundant. The ethyl acetate fraction contained phenols (103 mg/g) and tannins (69.56 mg/g) but lacked steroids and triterpenes. Antiplasmodial activity was evaluated in Plasmodium berghei-infected mice. The LD50 of the crude extract exceeded 5000 mg/kg, and significant dose-dependent suppression of parasitemia (p < 0.05) was observed at 250, 500, and 1000 mg/kg. These findings support the traditional use of T. brownii against malaria and encourage further studies on its bioactive fractions and compounds.